A laboratory study of electrical resistivity and consolidation properties of Kuantan bauxite deposits - Ahmad Fathiey, Razali (2019)
In Pahang, bauxite become an ecological disaster which start from 2015 until now. Malaysia annual output of bauxite ore has increased from over 200,000 tonnes in 2013 to nearly 20 million tonnes in 2015, becoming the world's top producer and accounting for nearly half of the supply to China's massive aluminium industry. Potential impacts are expected to go beyond physical environment and physical illness if the situation is not controlled. Consolidation of soil was widely reported by mainstream and social media. The issue of foundation engineering or the problem of existing buildings on soft ground become more terrible Consolidation of soil occurs when volume changes in saturated soil caused by the expulsion of pore water from loading. According to Karl Terzaghi consolidation is any process which involves decrease in water content of a saturated soil without replacement of water by air. This research will carry out laboratory test about electrical resistivity and consolidation properties of Kuantan bauxite deposits. The location of the bauxite sample for testing is taken from Bukit Goh, Indera Mahkota and Semambu. From each location, five samples are taken to be tested. This means that total of fifty samples from all location stated.